2018
DOI: 10.1103/physrevd.98.083023
|View full text |Cite
|
Sign up to set email alerts
|

Waveforms of compact binary inspiral gravitational radiation in screened modified gravity

Abstract: Scalar-tensor gravity, with the screening mechanisms to avoid the severe constraints of the fifth force in the Solar System, can be described with a unified theoretical framework, the so-called screened modified gravity (SMG). Within this framework, in this paper we calculate the waveforms of gravitational-waves (GWs) emitted by inspiral compact binaries, which include four polarization modes, the plus h+, cross h×, breathing h b , and longitudinal hL modes. The scalar polarizations h b and hL are both caused … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 63 publications
(152 reference statements)
0
64
0
Order By: Relevance
“…The sensitivity of a black hole in massive Brans-Dicke theory is s BH = 1 2 [22]. As a result, for a binary black hole system, Γ = S = 0 and the waveforms are identical to that of GR apart from the replacement M c → M c (1 − ξ) which are the same as that in the limit m s → ∞.…”
Section: Frequency-domain Gw Waveformsmentioning
confidence: 91%
See 1 more Smart Citation
“…The sensitivity of a black hole in massive Brans-Dicke theory is s BH = 1 2 [22]. As a result, for a binary black hole system, Γ = S = 0 and the waveforms are identical to that of GR apart from the replacement M c → M c (1 − ξ) which are the same as that in the limit m s → ∞.…”
Section: Frequency-domain Gw Waveformsmentioning
confidence: 91%
“…This is a result of the linearized scalar wave equation (16) [19,22]. Each of these two polarizations has two frequency modes.…”
Section: Gravitational Waves Generated By the Compact Binarymentioning
confidence: 99%
“…The results are consistent with Einstein's gravity as the analysis indicated that the pure tensor polarizations are favored over the scenario of pure vector or scalar polarizations. Nonetheless, the properties of the modified gravity regarding GWs have recently become a topic of increasing interest [19][20][21][22][23]. On the theoretical side, several methods can be employed to analyze the polarization modes of gravity theory.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work [32], we calculated the GWs energy flux in terms of derivatives of multipole moments in SMG, and derived the rate of the orbital energy loss for compact binaries in quasi-circular orbits. Based on it, in the literature [33], we calculated the waveforms of GWs emitted by inspiralling compact binaries. Recently, the eccentric GWs have been widely studied in the literature [34,35].…”
Section: Introductionmentioning
confidence: 99%